Suppressive Activity of Streptomycin on the Growth of Mycobacterium lepraemurium in Macrophage Cultures - Chang, Y. T. (1969)
The effect of streptomycin on the growth of an obligate intracellular bacterium was studied in a new host-parasite cell system. The system consisted of Mycobacterium lepraemurium grown in cultures of mouse peritoneal macrophages. Since these organisms do not grow in bacteriological media, the influence of extracellular bacterial growth can be ruled out. The suppressive activity of streptomycin was observed in a total of five experiments. At the end of 4 weeks, the average number of organisms per macrophage for the controls was 65.7; for cultures with streptomycin at concentrations of 0.5, 1, 5, 10, 50, and 100 μg/ml of medium, it was 45.4, 38.3, 28.7, 22.7, 13.4, and 8.2, respectively. A good dose-response relationship was evident. M. lepraemurium which had been treated in macrophage cultures with various concentrations of the antibiotic for 6 to 8 weeks was used to infect fresh macrophages. These cultures were in turn treated with streptomycin. Resistance of the organisms to streptomycin did not occur.